Individual and combined dietary exposure to polyethylene microplastics and cadmium in Litopenaeus vannamei: biological effects and bioaccumulation - Laura L. Bonilla-Aguirre; Gladys Valencia-Castañeda; Ofelia Escobar-Sánchez; Carmen C. Osuna-Martínez; Martín G. Frías-Espericueta; Alondra G. Rendon-Sánchez; Federico Páez-Osuna (Marine Environmental Research, 2026)

Copiapoa cacti as multitrophic interaction hubs and thermal refugia in the hyper-arid Atacama Desert - Sebastián Cordero; Bastián Unamuno; Catalina Escobar; Matías A. Vergara; Ignacia Roselló; Javiera Villarroel; Pablo C. Guerrero (Journal of Arid Environments, 2026)

State of deep-sea science and conservation in the Northeast Pacific: implications for policy and management - Fanny Girard; Joan M. Alfaro-Lucas; Amy R. Baco; James P. Barry; Katharine T. Bigham; Lara M. Beckmann; Angelika Brandt; Lindsay Clark; Megan A. Davies; Jeffrey C. Drazen; Anya Dunham; Cherisse Du Preez; et al. (Progress in Oceanography, 2026)

Lab-on-a-fruit: an approach for chemical evaluation of olive oil composition prior to extraction - Enrique C. Cabanas-Garrido; Mónica Calderón-Santiago; Feliciano Priego-Capote; Carlos A. Ledesma-Escobar (Food Chemistry, 2026)

Evaluating the phytotoxicity of sodium diclofenac treated with heterogeneous photocatalysis - J. T. dos Santos; L. B. G. A. Morselli; C. M. Pinheiro; V. L. Bobrowski; C. C. de Escobar; M. S. Quadro; R. Andreazza (International Journal of Environmental Science and Technology, 2026)
Pharmaceuticals are increasingly detected in surface water, and even at trace concentrations, they may pose ecological and health risks. In this study, heterogeneous photocatalysis using titanium dioxide (TiO 2 ) was applied under simulated solar irradiation to degrade sodium diclofenac. Irradiation times of 60, 120, and 180 min were used with a TiO 2 loading of 0.6 g L −1 . Under these conditions, only ~ 20% diclofenac degradation and 50% COD removal were achieved, indicating relatively low treatment efficiency. Cytotoxicity, genotoxicity, mutagenicity, and cytokinesis assays with Allium cepa did not reveal statistically significant toxic effects; however, some genotoxic responses were observed. Overall, no clear evidence of transformation products more harmful than the parent compound was detected, although this result should be interpreted with caution, given the observed genotoxic responses. Overall, heterogeneous photocatalysis exhibited limited performance under the tested conditions. Further studies with a broader experimental design and more detailed analytical approaches are required to confirm both its efficiency and safety.

Mussels enhance digestive enzyme activity in preparation for stressful fluctuating environments - Jordan A. James Bond; Petra I. Escobar; Newton Z. Hood; Helen C. Hong; Daniel R. Rankins; Grace Chan; Jade V. Betancourt; Karina Brocco French; Nichole D. Procter; Beck A. Wehrle; Kwasi M. Connor (Journal of Comparative Physiology B, 2026)
Elevated heat and low phytoplankton abundance are physiologically and ecologically challenging marine organisms of the northeast Pacific, including the mussel Mytilus californianus . During low tide, mussels are exposed to warm air and undergo anaerobic metabolism. Tidal variation coincides with daily fluctuations in food availability requiring flexible response systems (e.g., changes in digestive enzyme activity) to maintain homeostasis. In this study we allowed mussels to acclimate in tidal mesocosms with or without aerial heat across high and low levels of food abundance, after which we measured amylase (carbohydrase) activity and gene expression. Remarkably, enzyme activity was unpredictably elevated during low tide in fasted or moderate heat-stress (+ 8 °C; 23 °C) conditions, thereby potentially mitigating energy losses posed by environmental stress. Heat stress combined with fasting (multistressor) presented a marked challenge for mussels as evidenced by lower amylase activity compared to other treatments. A subsequent acute aerial heat-shock (+ 17 °C; 32 °C) negatively impacted amylase activity across all acclimation groups. Gene expression of amylase was anticorrelated with activity suggestive that mussels’ sense environmental fluctuations and respond by regulating digestive enzyme activity. Although mussels can employ these strategies to dampen short-term stress, the heatwaves predicted to persist in their ecosystems in the future may curtail their effectiveness.

Accumulation and damage of polyethylene-microplastics to the digestive system of juvenile Litopenaeus vannamei shrimp exposed through feed - Laura L. Bonilla-Aguirre; Ofelia Escobar-Sánchez; Carmen C. Osuna-Martínez; Martín G. Frías-Espericueta; Miguel Betancourt-Lozano; Selene M. Abad-Rosales; Rodolfo Lozano-Olvera; Federico Páez-Osuna; Gladys Valencia-Castañeda (Marine Pollution Bulletin, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Effect of microalgae and a cyanobacteria mixture on germinative activity, growth, and cannabinoid production in Cannabis sativa plants - Natalia Herrera; Tatiana C. Puentes-Escobar; Julian A. Álvarez-Pulido; Ronald Sanchez; Jelen Restrepo; Luis Fernando Echeverri (Journal of Applied Phycology, 2025)
The enhancement in agricultural productivity has been achieved through the application of pesticides and nutrients, mainly of synthetic origin. This practice has led to a dependence on the use of agrochemicals in order to obtain better results. However, the overuse application has created environmental and toxicological problems, so other alternatives are needed. For this reason, this study focused on evaluating the biostimulation of cannabis ( Cannabis sativa ) plants used in the production of cosmetics, pharmaceuticals, and phytotherapeutics through the application of three microalgae: Chlorella vulgaris , Ankistrodesmus falcatus , and Scenedesmus sp. and one cyanobacterium: Arthrospira platensis . This strategy aims to increase the cannabinoids production through a practical and environmentally friendly approach. In this way, crop quality can be improved while reducing fertilizers use, thus promoting more sustainable and efficient agricultural practices. Treatments combining nutrients and microalgae at different concentrations, a control in which only water was applied and a treatment containing only nutrients were used to assess seed germination, plant growth and the production of ten cannabinoids and other compounds present in the plants. The microalgae treatment alone stimulated germination processes in cannabis by 93%. The mixture of microalgae and cyanobacteria and the nutrients positively affected the growth of cannabis plants, increasing their length by up to 40% more than the control. Cannabinoid production was increased when the 50% nutrient mixture was used with the microalgae and cyanobacteria, resulting in increased production of five cannabinoids (CBD, Δ 9 -THC, CBDA, THCA, and Δ 8 -THC). These results demonstrate the potential of microalgae and cyanobacteria as sustainable biostimulants for cannabis cultivation. Graphical Abstract

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Phylogenetic and Functional Biogeographic Approach for Rodent Conservation Across an Environmental Gradient in Chile - Wendy C. Hernández‐Mazariegos; Felipe I. Torres; Reilly Brennan; Luis E. Escobar; R. Eduardo Palma; Christian M. Ibáñez (Journal of Biogeography, 2025)
Aim Understanding how abiotic factors influence species diversity, evolution and functional patterns of species is crucial for biodiversity conservation and for the management of terrestrial protected areas. We evaluate biogeographic and phylogenetic metrics in rodents to understand biodiversity patterns and improve wildlife conservation strategies. Location Chile, South America. Taxon Rodents (Mammalia, Rodentia). Methods We updated the phylogeny of rodent species in Chile using gene sequences retrieved from GenBank. We used the phylogenetic tree to calculate different biodiversity indices. We analysed Species Richness (SR), observed and standard effect size (SES) of Phylogenetic Diversity (PD), Phylogenetic Endemism (PE), and Functional Diversity (FD) across different ecoregions, climatic regions, and terrestrial protected areas along gradients of temperature and precipitation. Results We found high rodent diversity in north and central‐south Chile, and an association between phylogenetic and functional indices. Diversity indices (SR, SES.PD, SES.PE, SES.PE) were strongly associated with ecoregions, with the highest indices occurring in a high‐altitude ecoregion (i.e., Puna), Polar climatic region, and unprotected areas. Main Conclusions Spatial congruence among diversity indices suggests that species composition and evolutionary history play a fundamental role in structuring rodent species assemblages. Areas with high diversity indices delineate regions with high species richness that experience higher species diversification (PD), leading to ecological specialisation (FD) and endemism (PE). The linkages between diversity indices and ecoregions suggest that environmental heterogeneity within ecoregions drives variation in community composition. Environmental variation may be more pronounced in harsh habitats (e.g., Atacama Desert), while weak in benign habitats (e.g., Puna). The spatial mismatch between biodiversity hotspots and protected areas suggests that key evolutionary and ecological processes could be occurring outside current protected areas, raising concerns about the effectiveness of biodiversity conservation strategies.

Valorization of sludge from an industrial treatment plant as a carbocatalyst for degrading pharmaceuticals in aqueous solutions - Isabella Escobar; Camilo C. Castro-Jiménez; Jazmín Porras; María Isabel Mejía; Efraím A. Serna-Galvis; Sebastián Pérez; Juan Muñoz-Saldaña; Ricardo A. Torres-Palma; Nancy Acelas (Chemical Engineering Journal, 2025)

Building ocean acidification research and policy capacity in the wider Caribbean region: a case study for advancing regional resilience - Kalina C. Grabb; Natalie Lord; Kerri L. Dobson; Debbie-Ann D. S. Gordon-Smith; Elva Escobar-Briones; Marcia Creary Ford; Sylvia Lander; Gabriella D. Kitch; Melissa Meléndez; Julio Morell; Alain Muñoz Caravaca; Jan Newton; et al. (Frontiers in Marine Science, 2025)
To meet scientific, policy, and community goals, there is a critical need to strengthen research capacity, increase monitoring, and inform adaptation and mitigation policies to enhance resilience against ocean acidification (OA) and associated multi-stressors in the Caribbean. In 2023, an OA Needs Based Assessment survey of ocean professionals was conducted, engaging 59 participants from across the wider Caribbean to evaluate regional challenges and opportunities in OA research and monitoring. To understand differences in OA research capacity related to training and funding, we divide the respondents into four groups: those that have received 1) training and funding, 2) training only, 3) funding only, and 4) neither training nor funding. Results indicate regional strengths include awareness of local oceanic conditions, access to nearshore sites, and strong social support networks in ocean research. Regional barriers include limited technical capacity and funding to conduct oceanographic research and monitoring, and in particular, carbonate measurements. The four training and funding groups vary significantly, suggesting that access to training and funding are important factors to increasing the amount of access that respondents have to different types of equipment, the number of different types of measurements they conduct, the number of different habitats they research, and the amount of experience they have conducting OA research. This study also demonstrates the community-led efforts to address local OA challenges by presenting a case study on the formation of the Global Ocean Acidification Network (GOA-ON) OA Caribbean Hub that was founded by local leaders (co-authors of this study) who were inspired through the survey process and engagement that was conducted by co-authors. This study provides examples of avenues and challenges to build OA capacity for research and monitoring from the ground up within the wider Caribbean to advance towards global sustainability goals.

Diatomaceous Earth as Silicon Source Involved on Antioxidant, Morphology and Productive Traits of Hazelnut (Corylus avellana L.) - T. Escobar-Hernández; D. Padilla-Contreras; K. Godoy; B. Cayunao; C. Manterola-Barroso; D. Alarcón; A. Biško; C. Meriño-Gergichevich (Journal of Soil Science and Plant Nutrition, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Advances in Reproduction, Nutrition and Disease Research in the Yellowtail Kingfish ( Seriola lalandi ) Aquaculture - Alejandro S. Mechaly; Abigail Elizur; Sebastian Escobar‐Aguirre; Jorge Hirt‐Chabbert; Roxana Bertha Inohuye‐Rivera; Wayne Knibb; Josephine Nocillado; Juan C. Pérez‐Urbiola; H. K. A. Premachandra; Gustavo M. Somoza; Dariel Tovar‐Ramírez; Bin Wang (Reviews in Aquaculture, 2025)
Yellowtail kingfish ( Seriola lalandi ) is a species of significant value in aquaculture, with a broad distribution across subtropical and temperate seas. Although global production has doubled in 7 years, reaching approximately 9000 tons per year in 2021, its cultivation remains limited compared to other mainstream species. The commercial aquaculture of this species faces several key challenges in achieving improved production and sustainability: nutrition requirements, disease management, and the optimization of reproductive technologies. Current diets for yellowtail kingfish require further improvement to enhance both growth performance and sustainability. Diseases continue to be a major constraint, with at least 41 specific diseases reported for yellowtail kingfish and 31 affecting other Seriola species, emphasizing the necessity of targeted diagnostic tools and treatment strategies. Recent genomic advances have shed light on the biology and taxonomy of yellowtail kingfish, revealing genetically distinct populations across the South Pacific, Indian, and South Atlantic Oceans. However, the taxonomic status within the Pacific region remains unclear, requiring further research. Addressing these gaps is vital for developing robust breeding programs and improving genetic resilience. To support the sustainable expansion of yellowtail kingfish aquaculture, key areas for future research include increasing larval and juvenile survival rates, minimizing malformations, and tailoring farming models to diverse environmental conditions. Focusing on these priorities will ensure better productivity and disease resistance, ultimately promoting the global competitiveness of yellowtail kingfish as an aquaculture species.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Case report: ampullitis in Colombian Creole horse stallion - C.A. Camacho Rozo; J. Perez-Osorio; A. Paredes Cañon; C. Jimenez Escobar; J. Zambrano-Varón; H. Lozano; F. Soauza (Journal of Equine Veterinary Science, 2025)

Influence of climatic variables on biome transitions in the Colombian and Panamanian Caribbean region - Y. Nuñez-Bolaño; N. Hoyos; A. Correa-Metrio; C. Martínez; C. Pizano; J. Escobar; C. Huertas; C. Jaramillo (Global and Planetary Change, 2025)

Chirping across continents: variation in urban house sparrow (Passer domesticus) vocalizations across North America and Europe - Fernando González-García; Christine C. Rega-Brodsky; Michelle García-Arroyo; Pablo Bolaños Sittler; Juan Fernando Escobar-Ibáñez; Juan Hector García-Chávez; Marcus Hedblom; Ruben Heleno; Petar Iankov; Gintaras Malmiga; Alberto Martínez Fernández; Nancy E. McIntyre; et al. (Biological Invasions, 2025)
The house sparrow ( Passer domesticus ) is one of the most widespread invasive bird species, with numerous and dense populations established across urban-agricultural landscapes of North America. Although this species has been widely studied to identify the traits that explain its global ubiquity, descriptions of house sparrow acoustic features across its native and introduced range are limited in the literature. We recorded male house sparrow vocalizations from 13 cities across Europe and North America to quantify the structural features of its common “chirrup” vocalization. Although the basic structure and duration were consistent across the two geographic regions, the vocalizations differed in their minimum frequencies and bandwidth. In a post hoc analysis of 140 museum specimens, we found that European house sparrows had larger bills and bodies than those in North America. Thus, we propose that these frequency shifts could be a result of synergistic interactions between morphological differences, potential differences in ambient noise, acoustic overlap with other species within the soundscape, or other acoustic features of European and North American cities. House sparrows seem to be a good model for future bioacoustics studies, given their worldwide distribution and acoustic plasticity, to test hypotheses related to urbanization traits and invasion potential.

River Drying Causes Local Losses and Regional Gains in Aquatic Invertebrate Metacommunity Diversity: A Cross‐Continental Comparison - Daniel Escobar‐Camacho; Julie Crabot; Rachel Stubbington; Judy England; Romain Sarremejane; Núria Bonada; José María Fernández‐Calero; Miguel Cañedo‐Argüelles; Carla Ferreira Rezende; Pierre Chanut; Zoltán Csabai; Andrea C. Encalada; et al. (Global Change Biology, 2025)
Drying river networks include non‐perennial reaches that cease to flow or dry, and drying is becoming more prevalent with ongoing climate change. Biodiversity responses to drying have been explored mostly at local scales in a few regions, such as Europe and North America, limiting our ability to predict future global scenarios of freshwater biodiversity. Locally, drying acts as a strong environmental filter that selects for species with adaptations promoting resistance or resilience to desiccation, thus reducing aquatic α‐diversity. At the river network scale, drying generates complex mosaics of dry and wet habitats, shaping metacommunities driven by both environmental and dispersal processes. By repeatedly resetting community succession, drying can enhance β‐diversity in space and time. To investigate the transferability of these concepts across continents, we compiled and analyzed a unique dataset of 43 aquatic invertebrate metacommunities from drying river networks in Europe and South America. In Europe, α‐diversity was consistently lower in non‐perennial than perennial reaches, whereas this pattern was not evident in South America. Concomitantly, β‐diversity was higher in non‐perennial reaches than in perennial ones in Europe but not in South America. In general, β‐diversity was predominantly driven by turnover rather than nestedness. Dispersal was the main driver of metacommunity dynamics, challenging prevailing views in river science that environmental filtering is the primary process shaping aquatic metacommunities. Lastly, α‐diversity decreased as drying duration increased, but this was not consistent across Europe. Overall, drying had continent‐specific effects, suggesting limited transferability of knowledge accumulated from North America and Europe to other biogeographic regions. As climate change intensifies, river drying is increasing, and our results underscore the importance of studying its effects across different regions. The importance of dispersal also suggests that management efforts should seek to enhance connectivity between reaches to effectively monitor, restore and conserve freshwater biodiversity.

Thiolated hyper-crosslinked tetraphenylborate with tunable selectivity for sequential recovery of Pd and Pt from autocatalyst leachate - Erwin C. Escobar; John Edward L. Sio; Atul A. Pawar; Gebremedhn T. Gebremichael; Negasi T. Weldesemat; Hern Kim; Wook-Jin Chung; Grace M. Nisola (Chemical Engineering Journal, 2024)

A guide to the otoliths of Southern Ocean lanternfishes (Myctophidae) - Darren W. Stevens; Heather E. Braid; Laureline Meynier; Pablo C. Escobar-Flores; Matthew H. Pinkerton; Doug Hopcroft; Yanyu He; Yves Cherel (Polar Biology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

The dynamic changes in olive fruit phenolic metabolism and its contribution to the activation of quiescent Colletotrichum infection - H. Miho; A. Expósito-Díaz; M.I. Marquez-Perez; C. Ledesma-Escobar; C.M. Diez; D. Prusky; F. Priego-Capote; J. Moral (Food Chemistry, 2024)

Modeling the risk of aquatic species invasion spread through boater movements and river connections - Amy C. Kinsley; Szu‐Yu Zoe Kao; Eva A. Enns; Luis E. Escobar; Huijie Qiao; Nicholas Snellgrove; Ulirich Muellner; Petra Muellner; Ranjan Muthukrishnan; Meggan E. Craft; Daniel J. Larkin; Nicholas B. D. Phelps (Conservation Biology, 2024)
Aquatic invasive species (AIS) are one of the greatest threats to the functioning of aquatic ecosystems worldwide. Once an invasive species has been introduced to a new region, many governments develop management strategies to reduce further spread. Nevertheless, managing AIS in a new region is challenging because of the vast areas that need protection and limited resources. Spatial heterogeneity in invasion risk is driven by environmental suitability and propagule pressure, which can be used to prioritize locations for surveillance and intervention activities. To better understand invasion risk across aquatic landscapes, we developed a simulation model to estimate the likelihood of a waterbody becoming invaded with an AIS. The model included waterbodies connected via a multilayer network that included boater movements and hydrological connections. In a case study of Minnesota, we used zebra mussels ( Dreissena polymorpha ) and starry stonewort ( Nitellopsis obtusa ) as model species. We simulated the impacts of management scenarios developed by stakeholders and created a decision‐support tool available through an online application provided as part of the AIS Explorer dashboard. Our baseline model revealed that 89% of new zebra mussel invasions and 84% of new starry stonewort invasions occurred through boater movements, establishing it as a primary pathway of spread and offering insights beyond risk estimates generated by traditional environmental suitability models alone. Our results highlight the critical role of interventions applied to boater movements to reduce AIS dispersal.

Mercury in aquatic ecosystems of two indigenous communities in the Piedmont Ecuadorian Amazon: evidence from fish, water, and sediments - Daniel Escobar-Camacho; Daniela Rosero-López; Melany Ruiz-Urigüen; Karla S. Barragán; Natalia Carpintero-Salvador; José R. Daza; Allison Aldous; Silvia Benítez; Timothy Tear; Andrea C. Encalada (Ecotoxicology, 2024)
Mercury is a highly toxic element present in water, soil, air, and biota. Anthropogenic activities, such as burning fossil fuels, mining, and deforestation, contribute to the presence and mobilization of mercury between environmental compartments. Although current research on mercury pathways has advanced our understanding of the risks associated with human exposure, limited information exists for remote areas with high diversity of fauna, flora, and indigenous communities. This study aims to deepen our understanding of the presence of total mercury in water, sediments, and fish, within aquatic ecosystems of two indigenous territories: Gomataon (Waorani Nationality) and Sinangoé (Ai´Cofán Nationality) in the Ecuadorian Amazon. Our findings indicate that, for most fish (91.5%), sediment (100%) and water (95.3%) samples, mercury levels fall under international limits. For fish, no significant differences in mercury levels were detected between the two communities. However, eight species exceeded recommended global limits, and one surpassed the threshold according to Ecuadorian legislation. Piscivore and omnivore fish exhibited the highest concentrations of total mercury among trophic guilds. Only one water sample from each community’s territory exceeded these limits. Total mercury in sediments exhibited greater concentrations in Gomataon than Sinangoé. Greater levels of mercury in sediments were associated with the occurrence of total organic carbon. Considering that members of the communities consume the analyzed fish, an interdisciplinary approach, including isotopic analysis, methylmercury sampling in humans, and mercury monitoring over time, is imperative for a detailed risk assessment of mercury exposure in Amazonian communities.

Plastic pollution transcends marine protected area boundaries in the eastern tropical and south-eastern Pacific - Zara L.R. Botterell; Francisca Ribeiro; Daniela Alarcón-Ruales; Eliana Alfaro; Joanna Alfaro-Shigueto; Nicola Allan; Nicole Becerra; Laura Braunholtz; Susana Cardenas-Diaz; Diamela de Veer; Gabriela Escobar-Sanchez; Maria Virginia Gabela-Flores; et al. (Marine Pollution Bulletin, 2024)

Understanding inland fog and dew dynamics for assessing potential non-rainfall water use in the Atacama - F. Lobos-Roco; F. Suárez; F. Aguirre-Correa; K. Keim; I. Aguirre; C. Vargas; F. Abarca; C. Ramírez; R. Escobar; P. Osses; C. del Río (Journal of Arid Environments, 2024)

Interactions Between the Ubiquitin–Proteasome System, Nrf2, and the Cannabinoidome as Protective Strategies to Combat Neurodegeneration: Review on Experimental Evidence - Luis Angel Monsalvo-Maraver; Enid A. Ovalle-Noguez; Jade Nava-Osorio; Marisol Maya-López; Edgar Rangel-López; Isaac Túnez; Alexey A. Tinkov; Yousef Tizabi; Michael Aschner; Abel Santamaría; Diana C. Medrano-Cruz; Uriel García-Flores; et al. (Neurotoxicity Research, 2024)
Neurodegenerative disorders are chronic brain diseases that affect humans worldwide. Although many different factors are thought to be involved in the pathogenesis of these disorders, alterations in several key elements such as the ubiquitin–proteasome system (UPS), the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, and the endocannabinoid system (ECS or endocannabinoidome) have been implicated in their etiology. Impairment of these elements has been linked to the origin and progression of neurodegenerative disorders, while their potentiation is thought to promote neuronal survival and overall neuroprotection, as proved with several experimental models. These key neuroprotective pathways can interact and indirectly activate each other. In this review, we summarize the neuroprotective potential of the UPS, ECS, and Nrf2 signaling, both separately and combined, pinpointing their role as a potential therapeutic approach against several hallmarks of neurodegeneration. Graphical Abstract

Pesticides in soil, groundwater and food in Latin America as part of one health - Isabel Hilber; Fernando Bahena-Juárez; Aurea C. Chiaia-Hernández; Sebastián Elgueta; Arturo Escobar-Medina; Karen Friedrich; Miguel Ángel González-Curbelo; Yael Grob; Marisleydis Martín-Fleitas; Karina S. B. Miglioranza; Brizeidi Peña-Suárez; Nilda Pérez-Consuegra; et al. (Environmental Science and Pollution Research, 2024)
We here report of a conference about “Pesticides in Soil, Groundwater and Food in Latin America as part of One Health” that took place at the “IV Seminario Internacional de Sanidad Agropecuaria (SISA)” in Varadero, Cuba, 8–12 May 2023. Researchers of Latin America (Argentina, Brazil, Chile, Costa Rica, Colombia, Cuba, Mexico) and Switzerland (workshop initiator) held presentations about occurrence and effects of pesticides on the environment, human health, the replacement of highly hazardous pesticides (HHP) by agroecological alternatives and the agri-food value chain. In a subsequent round table discussion, the presenters identified deficits, needs, interests and opportunities. According to them, the lack of awareness of pesticide use affects the health and safety of workers applying the chemicals. Despite Latin America representing the main agricultural area in the world with a very intense pesticide use, monitoring data of pesticides in soil, surface and groundwaters, food, as well as in humans are missing. Risks of pesticides to humans should be assessed so that authorities can withdraw or limit within “short time” the access to corresponding formulations on the market. Also, communication is not state of the art and should be improved as, e.g. the teaching of workers and farmers, how to correctly use and apply pesticides or the briefing of decision makers. Pollinators suffer from multiple stressors not the least due to pesticides, and alternatives are badly needed. On the technical side, the different analytical methods to determine residues of active ingredients and transformation products in matrices of concern should be harmonized among laboratories. Seven future actions and goals were identified to overcome the above deficits. Next steps after the publishing of this conference report are to harmonize and complete the information status of the presenters by exchanging the results/data already present. Therefore, a platform of interaction to address issues described above and to enhance collaboration shall be created. Samples of different matrices shall be exchanged to harmonize the chemical analysis and establish interlaboratory comparisons. Such activities might be facilitated by joining international associations or organizations, where researchers can offer their expertise, or by forming a new pesticide network for Central and South America that could present tailored projects to national and international organizations and funding agencies.

Distribution of select per- and polyfluoroalkyl substances at a chemical manufacturing plant - Brian A. Schumacher; John H. Zimmerman; Alan C. Williams; Christopher C. Lutes; Chase W. Holton; Elsy Escobar; Heidi Hayes; Rohit Warrier (Journal of Hazardous Materials, 2024)

“Knitted” tetrabenzo-24-crown-8 ether sulfonate as reusable and practical hydrophilic adsorbent for aqueous Cs+ sequestration - John Edward L. Sio; Erwin C. Escobar; Grace M. Nisola; Khino J. Parohinog; Negasi T. Weldesemat; Hern Kim; Wook-Jin Chung (Journal of Environmental Chemical Engineering, 2024)

Genotyping of European Toxoplasma gondii strains by a new high-resolution next-generation sequencing-based method - M. Joeres; P. Maksimov; D. Höper; S. Calvelage; R. Calero-Bernal; M. Fernández-Escobar; B. Koudela; R. Blaga; M. Globokar Vrhovec; K. Stollberg; N. Bier; S. Sotiraki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose A new high-resolution next-generation sequencing (NGS)-based method was established to type closely related European type II Toxoplasma gondii strains. Methods T. gondii field isolates were collected from different parts of Europe and assessed by whole genome sequencing (WGS). In comparison to ME49 (a type II reference strain), highly polymorphic regions (HPRs) were identified, showing a considerable number of single nucleotide polymorphisms (SNPs). After confirmation by Sanger sequencing, 18 HPRs were used to design a primer panel for multiplex PCR to establish a multilocus Ion AmpliSeq typing method. Toxoplasma gondii isolates and T. gondii present in clinical samples were typed with the new method. The sensitivity of the method was tested with serially diluted reference DNA samples. Results Among type II specimens, the method could differentiate the same number of haplotypes as the reference standard, microsatellite (MS) typing. Passages of the same isolates and specimens originating from abortion outbreaks were identified as identical. In addition, seven different genotypes, two atypical and two recombinant specimens were clearly distinguished from each other by the method. Furthermore, almost all SNPs detected by the Ion AmpliSeq method corresponded to those expected based on WGS. By testing serially diluted DNA samples, the method exhibited a similar analytical sensitivity as MS typing. Conclusion The new method can distinguish different T. gondii genotypes and detect intra-genotype variability among European type II T. gondii strains. Furthermore, with WGS data additional target regions can be added to the method to potentially increase typing resolution.

Prediction of areas with high risk of roadkill wildlife applying maximum entropy approach and environmental features: East Antioquia, Colombia - J. Perez-Guerra; J. Gonzalez-Velez; J. Murillo-Escobar; J. C. Jaramillo-Fayad (Landscape and Ecological Engineering, 2024)
Linear infrastructures such as roads are known to cause adverse effects on the surrounding ecosystems. Wildlife–vehicle collisions (WVC) are considered to be one of the main causes of biodiversity loss. Several studies have demonstrated that WVC occurs on Colombian roads. However, studies have focused on a body count, the most affected species, and places with high mortality rates. We aim to propose a methodology for predicting WVC risk in the east of Antioquia, Colombia employing a machine learning approach to identify road segments with a high risk of WVC. Additionally, we present a novel validation technique for the "MaxEnt" approach. During this investigation, 499 reports were collected through road surveys between 2015 and 2016. We identified 160 road segments with high mortality rates with a 2D Hotspots analysis. 15 environmental descriptors were collected for each road segment. Validation of the predictive capabilities of the algorithm was performed using the area under the Receiver Operating Characteristic curve (AUC-ROC). The model achieved a good predictive ability (AUC>0.77). The response curves evidenced that features like distance to forest, land cover, resistance, and land use increase the probability of WVC, specifically, collision risk was higher in zones with high resistance values, crops, and pastures. This methodology has the potential to become an important tool for the prioritization of resources to mitigate WVC.

Valorization of ripe banana peels and cocoa pod husk hydrochars as green sustainable “low loss” dielectric materials - Andrea C. Landázuri; Luis M. Prócel; Oliver Caisaluisa; Katty Beltrán; Eduardo Holguín; Susan Yépez; Lourdes M. Orejuela-Escobar; Víctor H. Guerrero; Nelson Herrera; Ramiro Taco (Journal of Cleaner Production, 2023)

Landscape composition shapes biomass, taxonomic and functional diversity of dung beetles within human-modified tropical rainforests - Brenda Ratoni; Diana Ahuatzin; Erick J. Corro; Renato Portela Salomão; Federico Escobar; Juan C. López-Acosta; Wesley Dáttilo (Journal of Insect Conservation, 2023)

The evolution of the Maya coastal landscape in the Mexican Caribbean during the last 6200 years - A. Correa-Metrio; C. Cordero-Oviedo; E. Gámez-Núñez; G. Olivares-Casillas; J. Escobar; J.H. Curtis; L. Pérez; M. Blaauw; J.P. Bernal (Quaternary Science Reviews, 2023)

Morphology of buried volcanic bodies in a sedimentary basin of the Pacific Continental Shelf (Gulf of California, Mexico) - Mario González-Escobar; Abril C. Sánchez-Barra; Cristian A. Gallegos-Castillo; Sergio M. Arregui Ojeda; Edgar A. Mastache-Román (Journal of Volcanology and Geothermal Research, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Validating the occurrence of the giant mottled eel ( Anguilla marmorata ) in the Galápagos Islands - Daniel Escobar‐Camacho; Wilson Andrade; Nathalia Valencia; Andrea C. Encalada; Diana A. Pazmiño (Journal of Fish Biology, 2023)
The giant mottled eel ( Anguilla marmorata ) is distributed mostly in the Indo‐West Pacific. However, a few records indicate the presence of this eel in the Tropical Central and East Pacific. In April 2019, an eel specimen was caught in a small stream in San Cristobal Island, Galápagos. Morphological and molecular characters (16S and Cytb mtDNA sequences) confirmed the species as A. marmorata Quoy & Gaimard, 1824. The re‐discovery of A. marmorata in Galápagos supports the hypothesis of an eastward range expansion from the west, probably through the North Equatorial Counter‐Current.

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Eddies and fronts influence pelagic communities across the eastern Pacific ocean - Jessica N. Perelman; Yoann Ladroit; Pablo Escobar-Flores; E. Firing; Jeffrey C. Drazen (Progress in Oceanography, 2023)

Fluvial responses to late Holocene hydroclimate variability in the midcontinental United States - Maxwell N. Wright; Broxton W. Bird; Derek K. Gibson; Harvie Pollard; Jaime Escobar; Robert C. Barr (Quaternary Science Reviews, 2023)

Understanding climate change impacts on biome and plant distributions in the Andes: Challenges and opportunities - Carolina Tovar; Andrea F. Carril; Alvaro G. Gutiérrez; Antje Ahrends; Lluis Fita; Pablo Zaninelli; Pedro Flombaum; Ana M. Abarzúa; Diego Alarcón; Valeria Aschero; Selene Báez; Agustina Barros; et al. (Journal of Biogeography, 2022)
Aim Climate change is expected to impact mountain biodiversity by shifting species ranges and the biomes they shape. The extent and regional variation in these impacts are still poorly understood, particularly in the highly biodiverse Andes. Regional syntheses of climate change impacts on vegetation are pivotal to identify and guide research priorities. Here we review current data, knowledge and uncertainties in past, present and future climate change impacts on vegetation in the Andes. Location: Andes. Taxon: Plants. Methods We (i) conducted a literature review on Andean vegetation responses to past and contemporary climatic change, (ii) analysed future climate projections for different elevations and slope orientations at 19 Andean locations using an ensemble of model outputs from the Coupled Model Intercomparison Project 5, and (iii) calculated changes in the suitable climate envelope area of Andean biomes and compared these results to studies that used species distribution models. Results Future climatic changes (2040–2070) are projected to be stronger at high‐elevation areas in the tropical Andes (up to 4°C under RCP 8.5), while in the temperate Andes temperature increases are projected to be up to 2°C. Under this worst‐case scenario, temperate deciduous forests and the grasslands/steppes from the Central and Southern Andes are predicted to show the greatest losses of suitable climatic space (30% and 17%–23%, respectively). The high vulnerability of these biomes contrasts with the low attention from researchers modelling Andean species distributions. Critical knowledge gaps include a lack of an Andean wide plant checklist, insufficient density of weather stations at high‐elevation areas, a lack of high‐resolution climatologies that accommodates the Andes' complex topography and climatic processes, insufficient data to model demographic and ecological processes, and low use of palaeo data for distribution modelling. Main conclusions Climate change is likely to profoundly affect the extent and composition of Andean biomes. Temperate Andean biomes in particular are susceptible to substantial area contractions. There are, however, considerable challenges and uncertainties in modelling species and biome responses and a pressing need for a region‐wide approach to address knowledge gaps and improve understanding and monitoring of climate change impacts in these globally important biomes.

Sampling bias in multiscale ant diversity responses to landscape composition in a human-disturbed rainforest - D. A. Ahuatzin; D. González-Tokman; J. E. Valenzuela-González; F. Escobar; M. C. Ribeiro; J. C. L. Acosta; W. Dáttilo (Insectes Sociaux, 2022)

Moringa oleifera Lam. leaf powder antioxidant activity and cytotoxicity in human primary fibroblasts - Andrea C. Landázuri; Arleth Gualle; Verónica Castañeda; Emilia Morales; Andrés Caicedo; Lourdes M. Orejuela-Escobar (Natural Product Research, 2021)

Sheep herding in small grasslands promotes dung beetle diversity in a mountain forest landscape - C. Lucero Ríos-Díaz; Claudia E. Moreno; Ilse J. Ortega-Martínez; Iriana Zuria; Federico Escobar; Ignacio Castellanos (Journal of Insect Conservation, 2021)

Umbilical cord: an allogenic tissue for potential treatment of COVID-19 - Hugo C. Rodriguez; Manu Gupta; Emilio Cavazos-Escobar; Saadiq F. El-Amin; Ashim Gupta (Human Cell, 2021)

Metabolic acidosis and hyperkalemia differentially regulate cation HCN3 channel in the rat nephron - Zinaeli López-González; Teresa Padilla-Flores; Daniel León-Aparicio; Erika Gutiérrez-Vásquez; Carolina Salvador; Juan C. León-Contreras; Rogelio Hernández-Pando; Laura I. Escobar (Journal of Molecular Histology, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for dissipation of elements to the environment - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma; David Sanjuan-Delmás; Tobias C. Kampmann; Glenn Bark; Ainara Garcia Uriarte; Pierre Menger; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose The methods for assessing the impact of using abiotic resources in life cycle assessment (LCA) have always been heavily debated. One of the main reasons for this is the lack of a common understanding of the problem related to resource use. This article reports the results of an effort to reach such common understanding between different stakeholder groups and the LCA community. For this, a top-down approach was applied. Methods To guide the process, a four-level top-down framework was used to (1) demarcate the problem that needs to be assessed, (2) translate this into a modeling concept, (3) derive mathematical equations and fill these with data necessary to calculate the characterization factors, and (4) align the system boundaries and assumptions that are made in the life cycle impact assessment (LCIA) model and the life cycle inventory (LCI) model. Results We started from the following definition of the problem of using resources: the decrease of accessibility on a global level of primary and/or secondary elements over the very long term or short term due to the net result of compromising actions. The system model distinguishes accessible and inaccessible stocks in both the environment and the technosphere. Human actions can compromise the accessible stock through environmental dissipation, technosphere hibernation, and occupation in use or through exploration. As a basis for impact assessment , we propose two parameters: the global change in accessible stock as a net result of the compromising actions and the global amount of the accessible stock. We propose three impact categories for the use of elements: environmental dissipation, technosphere hibernation, and occupation in use, with associated characterization equations for two different time horizons. Finally, preliminary characterization factors are derived and applied in a simple illustrative case study for environmental dissipation. Conclusions Due to data constraints, at this moment, only characterization factors for “dissipation to the environment” over a very-long-term time horizon could be elaborated. The case study shows that the calculation of impact scores might be hampered by insufficient LCI data. Most presently available LCI databases are far from complete in registering the flows necessary to assess the impacts on the accessibility of elements. While applying the framework, various choices are made that could plausibly be made differently. We invite our peers to also use this top-down framework when challenging our choices and elaborate that into a consistent set of choices and assumptions when developing LCIA methods.

Bioaccumulation of mercury in Haemulopsis elongatus and Pomadasys macracanthus from the SE Gulf of California: condition indexes and health risk assessment - M. Ramos-Osuna; C. Patiño-Mejía; J. Ruelas-Inzunza; O. Escobar-Sánchez (Environmental Monitoring and Assessment, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Did earthquakes strike Machu Picchu? - M. A. Rodríguez-Pascua; C. Benavente Escobar; L. Rosell Guevara; C. Grützner; L. Audin; R. Walker; B. García; E. Aguirre (Journal of Seismology, 2020)

Bacillus subtilis EA-CB0575 genome reveals clues for plant growth promotion and potential for sustainable agriculture - Nicolás D. Franco-Sierra; Luisa F. Posada; Germán Santa-María; Magally Romero-Tabarez; Valeska Villegas-Escobar; Javier C. Álvarez (Functional & Integrative Genomics, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Regenerative and Resorbable PLA/HA Hybrid Construct for Tendon/Ligament Tissue Engineering - M. C. Araque-Monrós; D. M. García-Cruz; J. L. Escobar-Ivirico; L. Gil-Santos; M. Monleón-Pradas; J. Más-Estellés (Annals of Biomedical Engineering, 2020)

Estimates of density of mesopelagic fish in the Southern Ocean derived from bulk acoustic data collected by ships of opportunity - Pablo C. Escobar-Flores; Richard L. O’Driscoll; John C. Montgomery; Yoann Ladroit; Stefan Jendersie (Polar Biology, 2020)

Metal Concentrations in Age-Groups of the Clam, Megapitaria squalida, from a Coastal Lagoon in Mexico: A Human Health Risk Assessment - Carolina Delgado-Alvarez; Jorge Ruelas-Inzunza; Ofelia Escobar-Sánchez; Rodolfo Covantes-Rosales; Irving B. Pineda-Pérez; C. Cristina Osuna-Martínez; Marisela Aguilar-Júarez; J. Isidro Osuna-López; Domenico Voltolina; Martín G. Frías-Espericueta (Bulletin of Environmental Contamination and Toxicology, 2019)

Risk assessment of mercury in sharks (Rhizoprionodon longurio) caught in the coastal zone of Northwest Mexico - Martín G. Frías-Espericueta; Jorge Ruelas-Inzunza; Rubén Benítez-Lizárraga; Ofelia Escobar-Sánchez; C. Cristina Osuna-Martínez; Carolina G. Delgado-Alvarez; Marisela Aguilar-Juárez; J. Isidro Osuna-López; Domenico Voltolina (Journal of Consumer Protection and Food Safety, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Heavy Metal Bioaccumulation in the Anemone Paraphelliactis pabista Dunn, 1982 (Actiniaria: Hormathiidae) from the Hydrothermal System of Guaymas Basin, Gulf of California - M. Escobar-Chicho; L. A. Soto; C. Vanegas-Pérez; A. Estradas-Romero (Bulletin of Environmental Contamination and Toxicology, 2019)

Synthesis, anti-parasitic activity and QSAR study of a new library of polysubstituted tetrahydronaphtho[1,2-b]azepines - Andrés Felipe Yépes; Alí Bahsas; Patricia Escobar; Justo Cobo; Alirio Palma; Juan C. Garro Martinez; Ricardo Enriz (Medicinal Chemistry Research, 2018)

Measuring biodiversity in the Anthropocene: a simple guide to helpful methods - Claudia E. Moreno; Jaime M. Calderón-Patrón; Víctor Arroyo-Rodríguez; Felipe Barragán; Federico Escobar; Yuriana Gómez-Ortiz; Natalia Martín-Regalado; Ana P. Martínez-Falcón; Miguel Ángel Martínez-Morales; Eduardo Mendoza; Ilse J. Ortega-Martínez; Cisteil X. Pérez-Hernández; et al. (Biodiversity and Conservation, 2017)

Total mercury in muscles and liver of Mugil spp. from three coastal lagoons of NW Mexico: concentrations and risk assessment - C. G. Delgado-Alvarez; M. G. Frías-Espericueta; J. Ruelas-Inzunza; M. J. Becerra-Álvarez; C. C. Osuna-Martínez; M. Aguilar-Juárez; J. I. Osuna-López; O. Escobar-Sánchez; D. Voltolina (Environmental Monitoring and Assessment, 2017)

SNPs markers for the heavily overfished tambaqui Colossoma macropomum, a Neotropical fish, using next-generation sequencing-based de novo genotyping - José Gregorio Martínez; Valéria Nogueira Machado; Susana J. Caballero-Gaitán; Maria da C. Freitas Santos; Rodrigo Maciel Alencar; Maria Doris Escobar L.; Tomas Hrbek; Izeni Pires Farias (Conservation Genetics Resources, 2017)

Self‐fertilization, long‐distance flash invasion and biogeography shape the population structure of Pseudosuccinea columella at the worldwide scale - M. Lounnas; A. C. Correa; A. A. Vázquez; A. Dia; J. S. Escobar; A. Nicot; J. Arenas; R. Ayaqui; M. P. Dubois; T. Gimenez; A. Gutiérrez; C. González‐Ramírez; et al. (Molecular Ecology, 2017)
Population genetic studies are efficient for inferring the invasion history based on a comparison of native and invasive populations, especially when conducted at species scale. An expected outcome in invasive populations is variability loss, and this is especially true in self‐fertilizing species. We here focus on the self‐fertilizing Pseudosuccinea columella , an invasive hermaphroditic freshwater snail that has greatly expanded its geographic distribution and that acts as intermediate host of Fasciola hepatica , the causative agent of human and veterinary fasciolosis. We evaluated the distribution of genetic diversity at the largest geographic scale analysed to date in this species by surveying 80 populations collected during 16 years from 14 countries, using eight nuclear microsatellites and two mitochondrial genes. As expected, populations from North America, the putative origin area, were strongly structured by selfing and history and harboured much more genetic variability than invasive populations. We found high selfing rates (when it was possible to infer it), none‐to‐low genetic variability and strong population structure in most invasive populations. Strikingly, we found a unique genotype/haplotype in populations from eight invaded regions sampled all over the world. Moreover, snail populations resistant to infection by the parasite are genetically distinct from susceptible populations. Our results are compatible with repeated introductions in South America and flash worldwide invasion by this unique genotype/haplotype. Our study illustrates the population genetic consequences of biological invasion in a highly selfing species at very large geographic scale. We discuss how such a large‐scale flash invasion may affect the spread of fasciolosis.

Mercury and selenium concentrations in marine shrimps of NW Mexico: health risk assessment - M. G. Frías-Espericueta; B. Y. Ramos-Magaña; J. Ruelas-Inzunza; M. F. Soto-Jiménez; O. Escobar-Sánchez; M. Aguilar-Juárez; G. Izaguirre-Fierro; C. C. Osuna-Martínez; D. Voltolina (Environmental Monitoring and Assessment, 2016)

Got Dung? Resource Selection by Dung Beetles in Neotropical Forest Fragments and Cattle Pastures - A Bourg; F Escobar; I MacGregor-Fors; C E Moreno (Neotropical Entomology, 2016)

A New Synthetic Peptide with In vitro Antibacterial Potential Against Escherichia coli O157:H7 and Methicillin-Resistant Staphylococcus aureus (MRSA) - Y. A. Prada; F. Guzmán; P. Rondón; P. Escobar; C. Ortíz; D. A. Sierra; R. Torres; E. Mejía-Ospino (Probiotics and Antimicrobial Proteins, 2016)

Variations of body geometry in B rycon henni ( T eleostei: C haraciformes, B ryconidae) in different rivers and streams - N. Restrepo‐Escobar; J. C. Hurtado‐Alarcón; N. J. Mancera‐Rodríguez; E. J. Márquez (Journal of Fish Biology, 2016)
Landmark‐based geometric morphometrics were used to evaluate the effect of flow and depth in the water column on the body size and shape of Brycon henni from river and stream populations. The dendrogram showed that stream populations clustered apart and showed significantly smaller centroid size and narrower bodies than river populations, indicating a role for flow and depth on whole body morphometric variation. The results are concordant with morphometric variation described in other fish species and provide the first insights into phenotypic variation in natural populations of B. henni .

Exposure Assessment to Environmental Chemicals in Children from Ciudad Juarez, Chihuahua, Mexico - Angeles C. Ochoa-Martinez; Sandra T. Orta-Garcia; Edna M. Rico-Escobar; Leticia Carrizales-Yañez; Jorge D. Martin Del Campo; Lucia G. Pruneda-Alvarez; Tania Ruiz-Vera; Ana K. Gonzalez-Palomo; Iris G. Piña-Lopez; Arturo Torres-Dosal; Ivan N. Pérez-Maldonado (Archives of Environmental Contamination and Toxicology, 2016)

Apoptotic and autophagic cell death induced by glucolaxogenin in cervical cancer cells - L. Sánchez-Sánchez; M. L. Escobar; J. Sandoval-Ramírez; H. López-Muñoz; M. A. Fernández-Herrera; J. M. V. Hernández-Vázquez; C. Hilario-Martínez; E. Zenteno (Apoptosis, 2015)

Changes in Microbial Community Structure and Soil Biological Properties in Mined Dune Areas During Re-vegetation - Indra Elena C. Escobar; Vilma M. Santos; Danielle Karla A. da Silva; Marcelo F. Fernandes; Uided Maaze T. Cavalcante; Leonor C. Maia (Environmental Management, 2015)

Development and characterization of ten polymorphic microsatellites isolated from the scallop Argopecten purpuratus - C. J. MANDIOLA-QUILILONGO; M. A. RÍOS-RAMÍREZ; L. VELÁSQUEZ-CUMPLIDO; B. MORALES-MUÑOZ; J. A. ESCOBAR-FICA (Journal of Genetics, 2014)

First case of synophthalmia and albinism in the Pacific angel shark Squatina californica - O. Escobar‐Sánchez; X. G. Moreno‐Sánchez; C. A. Aguilar‐Cruz; L. A. Abitia‐Cárdenas (Journal of Fish Biology, 2014)
The first record in Mexican waters of albinism and synophthalmia (partial cyclopia) in the Pacific angel shark, Squatina californica is presented. Albinism is not lethal, but synophthalmia may cause the death of the individual immediately after birth.

Validation of a simple universal IELISA for the diagnosis of human brucellosis - S. M. Ayala; D. B. Hasan; C. A. Celestino; G. I. Escobar; D. M. Zhao; N. E. Lucero (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Mercury levels in myliobatid stingrays (Batoidea) from the Gulf of California: tissue distribution and health risk assessment - O. Escobar-Sánchez; J. Ruelas-Inzunza; J. C. Patrón-Gómez; D. Corro-Espinosa (Environmental Monitoring and Assessment, 2014)

Spatial distribution and concentration assessment of total petroleum hydrocarbons in the intertidal zone surface sediment of Todos os Santos Bay, Brazil - Carine S. Silva; Icaro T. A. Moreira; Olivia M. C. de Oliveira; Antonio F. S. Queiroz; Karina S. Garcia; Brunno A. Falcão; Narayana F. C. Escobar; Mariana Cruz Rios (Environmental Monitoring and Assessment, 2014)

Reconnaissance environmental magnetic study of urban soils, dust and leaves from Bogotá, Colombia - Bertha Aguilar Reyes; Victoria Mejía; Avto Goguitchaichvili; Jaime Escobar; Germán Bayona; Francisco Bautista; Juan C. Morales; Thomas J. Ihl (Studia Geophysica et Geodaetica, 2013)

Impairment of short term memory in rats with hepatic encephalopathy due to bile duct ligation - Renata Leke; Diogo L. Oliveira; Luiz F. Forgiarini; Thayssa D. C. Escobar; Thais O. Hammes; Fabíola S. Meyer; Susanne Keiding; Themis R. Silveira; Arne Schousboe (Metabolic Brain Disease, 2013)

Association of glutathione S-transferase Ω 1-1 polymorphisms (A140D and E208K) with the expression of interleukin-8 (IL-8), transforming growth factor beta (TGF-β), and apoptotic protease-activating factor 1 (Apaf-1) in humans chronically exposed to arsenic in drinking water - D. M. Escobar-García; L. M. Del Razo; L. C. Sanchez-Peña; P. B. Mandeville; C. Lopez-Campos; Claudia Escudero-Lourdes (Archives of Toxicology, 2012)

Mitral Valve Annuloplasty - Manuel K. Rausch; Wolfgang Bothe; John-Peder Escobar Kvitting; Julia C. Swanson; D. Craig Miller; Ellen Kuhl (Annals of Biomedical Engineering, 2012)

Bioaccumulation and Biomagnification of Total Mercury in Four Exploited Shark Species in the Baja California Peninsula, Mexico - A. Maz-Courrau; C. López-Vera; F. Galván-Magaña; O. Escobar-Sánchez; R. Rosíles-Martínez; A. Sanjuán-Muñoz (Bulletin of Environmental Contamination and Toxicology, 2012)

Characterization of Mitral Valve Annular Dynamics in the Beating Heart - Manuel K. Rausch; Wolfgang Bothe; John-Peder Escobar Kvitting; Julia C. Swanson; Neil B. Ingels; D. Craig Miller; Ellen Kuhl (Annals of Biomedical Engineering, 2011)

Isolation and characterisation of polymorphic microsatellite markers for the endangered ferreous limpet Patella ferruginea (Gastropoda, Patellidae) - A. Machordom; U. Ramírez-Escobar; I. Acevedo; R. García-Jiménez; P. Cabezas; M. Calvo; C. Toledo; P. Bloor (Conservation Genetics, 2010)

Analysis of different cell death processes of prepubertal rat oocytes in vitro - M. L. Escobar; O. M. Echeverría; L. Sánchez-Sánchez; C. Méndez; E. Pedernera; G. H. Vázquez-Nin (Apoptosis, 2010)

Cytological damage of nasal epithelium associated with decreased glutathione peroxidase in residents from a heavily polluted city - S. A. Hernández-Escobar; M. C. Ávila-Casado; V. Soto-Abraham; O. L. López Escudero; M. E. Soto; M. L. Vega-Bravo; T. Fortoul van der Goes; Elba Reyes-Maldonado (International Archives of Occupational and Environmental Health, 2009)

Identification of naturally processed ligands in the C57BL/6 mouse using large-scale mass spectrometric peptide sequencing and bioinformatics prediction - Julio C. Delgado; Hernando Escobar; David K. Crockett; Eduardo Reyes-Vargas; Peter E. Jensen (Immunogenetics, 2009)

Genotypic, phenotypic, and clinical characteristics of isolates ofHelicobacter pylori from San Luis, Argentina - C. M. Mattana; A. E. Vega; F. Escobar; L. Sabini; S. Zanón; O. N. Puig de Centorbi (Folia Microbiologica, 2007)

Skin tumors among employees of a tar refinery: the current data and their implications - S. Voelter-Mahlknecht; R. Scheriau; G. Zwahr; B. Koch; L. C. Escobar Pinzon; H. Drexler; S. Letzel (International Archives of Occupational and Environmental Health, 2007)

First experiences with DIN ISO 14835-1 in the context of vibration-induced white finger disease - S. Voelter-Mahlknecht; F. Krummenauer; D. Koulele; U. Mahlknecht; L. C. Escobar Pinzón; H. Dupuis¹; S. Letzel (International Archives of Occupational and Environmental Health, 2006)

Bacteremia by Streptobacillus moniliformis: First Case Described in Spain - L. Torres; A. I. López; S. Escobar; C. Marne; M. L. Marco; M. Pérez; J. Verhaegen (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Transient expression of Arabidopsis thaliana ascorbate peroxidase 3 in Nicotiana benthamiana plants infected with recombinant potato virus X - C. Escobar; L. E. Hernández; A. Jiménez; G. Creissen; M. T. Ruiz; P. M. Mullineaux (Plant Cell Reports, 2003)

Selecting plants to minimise radiocaesium in the food chain - Philip J. White; Kamal Swarup; Abraham J. Escobar-Gutiérrez; Helen C. Bowen; Neil J. Willey; Martin R. Broadley (Plant and Soil, 2003)

Metabolic correlates of the circadian pattern of suckling-associated arousal in young rabbits - C. Escobar; R. Hudson; M. Martínez-Gómez; R. Aguilar-Roblero (Journal of Comparative Physiology A, 2000)

Can in vitro biology have farm-level impact for small-scale cassava farmers in Latin America? - A. M. Thro; W. M. Roca; J. Restrepo; H. Caballero; S. Poats; R. Escobar; G. Mafla; C. Hernandez (In Vitro Cellular & Developmental Biology - Plant, 1999)

Over-expression of the oat arginine decarboxylase cDNA in transgenic rice (Oryza sativa L.) affects normal development patterns in vitro and results in putrescine accumulation in transgenic plants - T. Capell; C. Escobar; H. Liu; D. Burtin; O. Lepri; P. Christou (Theoretical and Applied Genetics, 1998)

A comparison of the adrenal cortical response to ACTH stimulation in Angora and non-Angora goats - C. Jiménez Escobar; P.K. Basrur; C. Gartley; R.M. Liptrap (Veterinary Research Communications, 1998)